Landscape Dynamics of Oak-Savanna in the Lower Chippewa River Valley, Wisconsin - Sigrist, Anthony (My University, 2013)
The Caryville Savanna in Dunn County, Wisconsin, was visited on five days in June 2012. The preliminary data suggests that fluvial geomorphology plays a key role in oak savanna establishment on the Caryville Savanna. The purpose of this study was to better understand the landscape drivers of oak savanna.
Color poster with text, images, tables, graphs, and maps.
Keywords: Chippewa River Valley (Wis.)--Landscape; Oak savanna--Study of; Posters